«Покарання» та «намір» в канонічному праві: сподівання П’єра Абеляра - Шевченко, А.Є.; Туренко, О.С. (Альманах права, 2012)
У статті розглядається концептуальні основи першої спроби в історії західноєвропейської юриспруденції розрізнити поняття «покарання» та «намір». Ця спроба була реалізована канонічним правом і ґрунтувалася на етичній доктрині П. Абеляра, який мав сподівання на те, що його вчення перетворить людину з
об’єкта впливу на суб’єкта вільної волі та права. В статье рассматривается концептуальные основы первой попытки в истории западноевропейской юриспруденции различить понятие «наказания» и «намерение». Эта попытка была реализована каноничным правом и основывалась на этической доктрине П. Абеляра, который имел надежду на то, что его учение превратит человека из объекта влияния, в субъект свободной воли и права. An ethical teaching of Abelard is one of the first attempts of Western European intellectuals to distinguish the concept of sin and legal offenses. Theologian offers a vital rule: «Understand that trust», and relying on it formulates the principles of moral subjectivism — individual responsibility of man for his actions and is a concept whereby a person can overcome his vicious nature and to identify the virtuous path of salvation. Thus, a reasonable person’s ability, inclination of the soul to good Abelard puts it above the sinful heredity. Thus, a person becomes an object of influence on the free subject.
In the notion of Abelard sin — a layman contempt for God, sin — it is conscious or unconscious action that does not conform to the principles of the faith of the individual. Sin is less likely related to the natural depravity of man, from its original sin, and carries a subjective, social nature. It appears at a moment when a person departs from
his convictions. This is a violation of social norms defined the right to consent rights for illegal action. Conscious rejection of beliefs and values, that individual long used in life is the hardest sin. Unconscious sin is an act that was committed through ignorance. In this case, a single act does not take a moral guilt before God, and therefore can not be punished because God judges a man not so much of our deeds, and because of that soul she did this act. Sin through ignorance is overcome Sacrament and, most importantly, conscious repentance, indicating layman in his emotional and mental imperfection, mobilizing it in a thorough self-control and virtuous life within the limits of the church community. However, unconscious sin can cause damage to the
community or individual. In this case, the person who committed a crime should be punished earthly court. Thus, Abelard sin divides into two levels — supernatural level, where the only judge is God and the earthly level court that
determines guilt and punishment for the crimes subject of the action within legal norms.
Abelard defines sinful choices as the notion of «intention». This term allows the thinker to realize the difference between sins of legal violations. It takes moral evaluation of the results of intention, internal basis performed an act that is the definition of reason, guided man before the act. All struggle, all the contradictions that unfold in the
human soul, in his conscience. Thus, the concept of «intention» and «punishment» separated thinker. Intention is moral and religious sphere of life of the individual. It may be known to other individuals and, in spite of its vicious nature is punished ecclesiastical court, but morally defendant church community as judges can only external manifestation of the act — that the action violates the social order. In this case, the punishment must match the intent of the individual not as the evil done to the community. Thus Abelard’s ordering is concept sinful intention
and legal offenses, legal decisions. Last governed social order is preserving harmony and justice in the community. This thinker paid attention that legal decisions should recognize and take into account the intention of the person.
So, first, the canon law begins to share the religious notion of sin and crime as a social force, and secondly, the prerogative of earthly justice is external performance against common expectations; Third, the church court should divide the external action and intention of the individual, his conviction, the fourth , a church court may consider
intention only in extreme cases where convictions laity are signs of «deadly sin»; Fifth, the court had the attributes of objectivity, it should analyze and identify the person intends to measure its jurisdiction; Sixth, punishment must be proportional the crime, it is necessary to account of intention. Thus, separation of moral guilt and legal violations
that took place over the definition of «intent» in the ethical teachings of Abelard, followed by canonists’ twelfth century, reveals humanistic aspirations of intellectuals in the transformation of an object with influence on the subject of free will and right. This principle is the foundation of modern European law and the basis for formation
responsible for their lives and actions of the individual.